Pengaruh Kinerja Keuangan TerhadapProfitabilitas dengan Financial Leverage Sebagai Variabel Moderasi pada Bank Umum Syariah - M. Aji Aditiya Pranata; Fuad Hasyim (Al Iqtishod: Jurnal Pemikiran dan Penelitian Ekonomi Islam, 2024)
The Covid-19 pandemic has become a major obstacle for sharia-based banks in maintaining their profitability without having to take out additional loans. The aim of this study is to investigate the impact of financial performance, as measured by OCR, CAR, FDR, and NPF proxies, on profitability by considering the Financial Leverage variable as a moderating factor in Sharia Commercial Banks. The population in this study includes all Sharia Commercial Banks that publish financial reports to the Financial Services Authority (OJK) for the 2018-2022 period. The sample obtained included 12 Sharia commercial banks that met the criteria based on. Data analysis used multiple linear regression methods for the fixed-effect model (FEM) selection panel data. The findings indicate that OCR and NPF have a significant Return on Assets (ROA), while CAR and FDR do not have a significant effect on ROA. In addition, through the Moderated Regression Analysis (MRA) test, it was found that DER acts as a moderating variable that influences the relationship between CAR, FDR, and NPF on ROA but does not influence the relationship between OCR and ROA. This research proves that financial leverage by considering debt can be an indicator for measuring financial performance towards profitability.